2011
DOI: 10.1136/emermed-2011-200610
|View full text |Cite
|
Sign up to set email alerts
|

Validating the acute heart failure index for patients presenting to the emergency department with decompensated heart failure

Abstract: Background The Acute Heart Failure Index (AHFI) is a previously derived prediction rule to identify patients presenting to emergency departments (EDs) with decompensated heart failure (DHF) at low risk for early life-threatening events. Study Objectives We sought to prospectively validate the AHFI. Methods Using a prospective cohort study, we included adult patients presenting to an urban university hospital ED with DHF. We gathered data on 21 variables to calculate the AHFI. Primary endpoints included inp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Interviews with staff suggested that education efforts were inadequate for these patients and were characteristically delayed until the end of their admissions. Previous studies on our population confirmed lack of adherence to medication regimens to be a strong predictor of admission for decompensation [14], and that almost all heart failure patients presenting to our emergency room were admitted to the hospital [15].…”
Section: Methodssupporting
confidence: 70%
See 1 more Smart Citation
“…Interviews with staff suggested that education efforts were inadequate for these patients and were characteristically delayed until the end of their admissions. Previous studies on our population confirmed lack of adherence to medication regimens to be a strong predictor of admission for decompensation [14], and that almost all heart failure patients presenting to our emergency room were admitted to the hospital [15].…”
Section: Methodssupporting
confidence: 70%
“…Clinical prediction rules for stratifying risk of readmission, mortality Several prediction instruments have been developed for patients with DHF [20,38]. One has been validated in the authors' centre [15].…”
Section: Adapting Protocols Found In Evidence Reviewmentioning
confidence: 99%
“…The acute HF index is calculated from 21 prognostic indicators (eg, demographics, past medical history, vital signs, laboratory data, and ECG and radiology findings). 85 An algorithm dichotomizes patients into subgroups of low or high risk for mortality, serious medical complications, and rehospitalization within 30 days. Second, the Evaluation Study of Congestive HF and Pulmonary Artery Catheterization Effectiveness risk model and discharge score 86 extend previous research of patient risk factors at discharge.…”
Section: High-risk Patient Identification With Risk Modelsmentioning
confidence: 99%
“…Given the poor outcomes associated with repeat ER visits and readmissions for HF, better strategies of risk stratification in the ER have been developed. 4,23 One of these, the Emergency Heart Failure Mortality Risk Grade, combines multiple point-of-care clinical parameters to guide admission decisions in the ER. This risk score has now been turned into an online calculator to assist ER physicians in assessing risk for a single HF visit.…”
Section: Discussionmentioning
confidence: 99%